The role of dimensions of social capital and sports participation in the social vitality of participants in public sports in Guilan - Saneie , Parisa; Molaeifard Pileh Rood, Fatemeh; Mehri , Kazem (Social Determinants of Health, 2024)
Background: Social vitality, as one of the important indicators of quality of life, plays a key role in improving public welfare and social dynamics. Social capital and sports participation were among the most important variables affecting social vitality. The aim of this study was identifying and analyzing the importance of social capital and sports participation on the social vitality of participants in public sports. Methods: This study was descriptive and participants were the managers of the General Department of Sports and Health of Guilan, 11 people were selected to answer the questions of the questionnaire using the purposeful sampling method. In this study, initially by reviewing the theoretical foundations, dimensions of social capital and sports participation were identified. By using the Interpretive Structural Modeling method, the relationships between these factors were determined and the factors were prioritized in 8 levels. Results: The results showed that cohesion, acceptability, and social networks are at the first level, social norms at the second level, social trust at the third level, activity repetition and activity duration at the fourth level, social participation and individual motivation at the fifth level, activity intensity at the sixth level, social support, access, activity context, and level of participation at the seventh level, and finally, type of activity at the eighth level of social capital. Conclusion: The dimensions of social capital are deeply intertwined with sports participation, enhancing both individual experiences and community dynamics The results of this research can help decision makers and policy makers in designing effective social policies to improve social vitality.